Radiomics in Glioblastoma: Current Status and Challenges Facing Clinical Implementation - Chaddad, Ahmad; Kucharczyk, Michael Jonathan; Daniel, Paul; Sabri, Siham; Jean-Claude, Bertrand J.; Niazi, Tamim; Abdulkarim, Bassam (Frontiers in Oncology, 2019)
Radiomics analysis has had remarkable progress along with advances in medical imaging, most notability in central nervous system malignancies. Radiomics refers to the extraction of a large number of quantitative features that describe the intensity, texture and geometrical characteristics attributed to the tumor radiographic data. These features have been used to build predictive models for diagnosis, prognosis, and therapeutic response. Such models are being combined with clinical, biological, genetics and proteomic features to enhance reproducibility. Broadly, the four steps necessary for radiomic analysis are: 1) image acquisition, 2) segmentation or labeling, 3) feature extraction, and 4) statistical analysis. Major methodological challenges remain prior to clinical implementation. Essential steps include: adoption of an optimized standard imaging process, establishing a common criterion for performing segmentation, fully automated extraction of radiomic features without redundancy, and robust statistical modeling validated in the prospective setting. This review walks through these steps in detail, as it pertains to high grade gliomas. The impact on precision medicine will be discussed, as well as the challenges facing clinical implementation of radiomic in the current management of glioblastoma.